Circulating micronutrient levels and their association with sepsis susceptibility and severity: a Mendelian randomization study - Wei, Zhengxiao; Liu, Yingfen; Mei, Xue; Zhong, Jing; Huang, Fuhong (Frontiers in Genetics, 2024)
Previous research has paid limited attention to the role of trace micronutrients in the pathogenesis of sepsis. Therefore, we employed Mendelian randomization analysis to comprehensively investigate the causal relationship between the levels of nine micronutrients (including calcium, βcarotene, iron, magnesium, phosphorus, vitamin C, vitamin B6, vitamin D, and zinc) and susceptibility, severity, and subtypes of sepsis. Our research indicates that zinc might have a safeguarding effect in decreasing the likelihood of death within 28 days for patients with severe sepsis, endorsing the medical recommendation of providing zinc supplements to patients who face a high risk of mortality due to severe sepsis. This provides new insights for further research into the role of micronutrients in the prevention and treatment of sepsis.